Survey of Home Cleaning Practices With Noninvasive Ventilation Equipment. Issue 2 (7th April 2023) - Qu, Yiwei; Milross, Maree; McGuiness, Olivia; Menadue, Collette; Piper, Amanda
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: Home noninvasive ventilation (NIV) equipment is often observed to be dirty, potentially increasing patients' risk of respiratory infection. This study aimed to describe the cleaning practices of home NIV patients. Methods: This single-site, cross-sectional, observational study surveyed 100 patients from the respiratory failure clinic regarding cleaning instructions, cleaning habits, barriers, and motivators to cleaning. Open-ended responses were analyzed with basic content analysis and closed categorical responses with frequencies and percentages. Results: Of 100 participants, 77% responded. Cleaning instructions most commonly recalled included cleaning with soapy water for masks (26/47, 55%), head straps (19/47, 40%), and tubing (21/47, 45%); vinegar solution for humidifiers (9/39, 23%); and replacing filters (14/39, 36%). Fourteen respondents reported barriers to cleaning, including forgetfulness (7/14, 50%) and physical difficulties (6/14, 43%). Commonly reported cleaning practices included soapy water to soak masks (28/77, 36%) and tubing (35/77, 46%), weekly masks (34/77, 44%) and tubing cleaning (29/77, 38%), vinegar solution to clean humidifiers for the 36 humidifier users (15/36, 44%), monthly humidifier cleaning (13/36, 36%), and monthly filter cleaning/replacement (36/77, 47%). Conclusion: Few respondents could recall specific instructions about when and how to clean their equipment. Many reported routine cleaning, with varied methods and frequencies. Our results will inform future NIV equipment cleaning educational package design.